2017
DOI: 10.1891/1052-3073.28.1.129
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Financial Advice Certification on Investment Choices

Abstract: The purpose of this study is to investigate whether a professional designation affects consumer choice behavior within the area of investment decision making. Forty-six participants were endowed with real money and received hypothetical investment advice from a certified financial planner (CFP) Professional and a stockbroker. Among low-income households, advice from a CFP altered investor choice behavior within hypothetical education and retirement savings accounts. When participants made investment decisions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Financial and economic researchers have emphasized financial guidance as a very effective replacement for financial knowledge, and they also claimed that it influences the decision to purchase financial goods and services (Calcagno & Monticone, 2015; Cwynar et al, 2020). Researchers have also suggested that receiving financial guidance from a qualified adviser can improve investment outcomes (Guillemette & Jurgenson, 2017). Some of the current literature on migrant behavior have also highlighted how migrants themselves recognize the need for effective financial advice (Natoli, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Financial and economic researchers have emphasized financial guidance as a very effective replacement for financial knowledge, and they also claimed that it influences the decision to purchase financial goods and services (Calcagno & Monticone, 2015; Cwynar et al, 2020). Researchers have also suggested that receiving financial guidance from a qualified adviser can improve investment outcomes (Guillemette & Jurgenson, 2017). Some of the current literature on migrant behavior have also highlighted how migrants themselves recognize the need for effective financial advice (Natoli, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…According to various writers in the field, financial advice could replace financial literacy because it influences a person's financial decisions concerning financial goods and services (Cwynar et al, 2020;Nguyen & Rozsa, 2019). Previous studies also found that whenever guidance from a qualified financial advisor is obtained, even risk-averse consumers change their investment behavior, increasing the value of the financial decision (Guillemette & Jurgenson, 2017). When offered the chance to attend any lesson on enhancing financial knowledge, researchers performed tests and concluded that most migrants are uninterested in financial advice and that it has no impact on their financial choices, thereby impacting their remittance behavior (Natoli, 2015(Natoli, , 2018.…”
Section: Financial Anxiety Positively Affects Migrant Remittance From...mentioning
confidence: 99%
“…The researchers in the past have also argued upon online resources and experts being an extremely vital source of good and sound financial advice (Çera et al, 2020;van Rooij et al, 2011). The researchers have also argued that advice received from a certified financial expert has an important influence on risk perception and trust of investors causing them to invest more (Guillemette & Jurgenson, 2017). As a result, it appears that there exists a link between internet exposure and financial advice (Khan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety arises from the worry of losing money as a result of a poor investment decision (Cwynar et al, 2020) that can be controlled by online expert advice (Cwynar et al, 2020). As we have already discussed that experts' opinion affects the trust level in investment decision and thereby has a positive impact on investments (Guillemette & Jurgenson, 2017), furthermore, the digital platform provides good and reliable assistance in the form of online resources and expert counsel ( van Rooij et al, 2011) and peers' opinion (Rambe & Jafeta, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation